HUBUNGAN PENERAPAN PROGRAM K3 TERHADAP KEPATUHAN PENGGUNAAN APD PADA PEKERJA KONSTRUKSI DI PEMBANGUNAN GEDUNG PARKIR BANDARA AHMAD YANI SEMARANG - Hayu Astiningsih; Bina Kurniawan; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Some violations against safety rule are seen every day at the airport Project in Semarang although the management implements an Occupational Safety and Health (OSH) program such as: safety induction, safety meeting, safety inspection, safety patrol, safety supervision, safety morning, toolbox meeting, personal protective equipment and housekeeping (5R). this research was meant to analyse the association between OSH implementation and the discipline in using personal protective equipment (PPEs). This research utilized observation with cross-sectional approach. A 74 employees were requested to participate in this study. Checklist and questionnaires were distributed. The results showed that there was an association between safety inspection and the use of PPEs (p = 0,024; α=0,05); safety supervision and the use of PPEs (p = 0,024; α=0,05); safety morning and the use of PPEs (p = 0,043; α=0,05). However, toolbox meeting as not associated ith the use of PPEs (p = 0,251; α=0,05). OSH program is useful for enforcing the use of PPEs.